A dedicated respiratory function monitor to improve tidal volume delivery during neonatal anesthesia. Issue 9 (12th August 2019) - Atkins, William K.; McDougall, Rob; Perkins, Elizabeth J.; Pereira‐Fantini, Prue M.; Tingay, David G.
Abstract: Background: Tight control of tidal volume using accurate monitoring may improve neonatal outcomes. However, respiratory function monitors incorporated in current anesthetic workstations are generally inaccurate at tidal volumes used for infants. Aims: To determine if a specific respiratory function monitor for neonatal infants improved expired tidal volume delivery during anesthesia. Method: Infants <3 months old requiring intubation for surgery in the operating theater were studied. After intubation a Phillips NM3, Acutronic Florian, or Novametrix Ventcheck Respiratory Function Monitor was integrated into the circuit, and clinicians given access to the display for the duration of anesthesia. Breath‐to‐breath expired tidal volume delivery, leak, and delivered pressure were recorded, with cardiorespiratory parameters. These were compared with a matched control group with clinicians blinded to respiratory function monitor display. Results: A total of 10 055 and 2569 inflations were measured in the respiratory function monitor visible (n = 32) and masked (n = 33) groups, respectively, with mean (standard deviation) delivered expired tidal volume 7.5 (2.4) mL/kg and 7.7 (3.0) mL/kg, respectively; mean difference (95% confidence interval) −0.2 (−1.1, 0.8) mL/kg (Welch's t test). In the visible group, 55.6% of expired tidal volumes were between 4 and 8 mL/kg compared to 51.7% in the masked group; relative benefit (95% confidence interval), 1.08 (1.03, 1.12). Expired tidal volume was less likely to be <4 mL/kg in the visible group compared to masked group; 6.4% vs 9.8%, 1.53 (1.33, 1.76). The use of a respiratory function monitor also reduced the number of inflations >10 mL/kg; 13.0% vs 22.0%, 1.11 (1.09, 1.14). Conclusion: Tidal volumes <4 mL/kg and >10 mL/kg are frequently delivered during neonatal anesthesia. The inclusion of an accurate respiratory function monitor may reduce the risk of exposure to potentially harmful tidal volumes.